2014
DOI: 10.1016/j.childyouth.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Online communication, social media and adolescent wellbeing: A systematic narrative review

Abstract: Background: Much debate and polarisation exists regarding the impact of online social technologies on the mental wellbeing of young people. Objective: To systematically review and synthesise current empirical research on this topic, identifying both the beneficial and harmful effects of online communication and social media technology amongst young people. Methods: A systematic narrative review of research published between January 2003 and April 2013, retrieved using rigorous searching on eight bibliographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
546
5
23

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 825 publications
(653 citation statements)
references
References 83 publications
28
546
5
23
Order By: Relevance
“…31 Some of the harmful social media effects that are reported in previous research on adolescents and children include "social isolation, depression and cyber-bullying." 32 In a large-scale study that involved about 10,000 EU children, the respondents themselves reported certain types of risks that they find on the Internet including pornography, cyber-bullying, and violent content. 33 Other types of harmful effects include "poor self-rating of mental health and experiences of high levels of psychological distress and suicidal ideation."…”
Section: Video Games and Terrorismmentioning
confidence: 99%
“…31 Some of the harmful social media effects that are reported in previous research on adolescents and children include "social isolation, depression and cyber-bullying." 32 In a large-scale study that involved about 10,000 EU children, the respondents themselves reported certain types of risks that they find on the Internet including pornography, cyber-bullying, and violent content. 33 Other types of harmful effects include "poor self-rating of mental health and experiences of high levels of psychological distress and suicidal ideation."…”
Section: Video Games and Terrorismmentioning
confidence: 99%
“…This grouping of texts provided an overview of included literature and enabled further analysis to be grounded in data by being used as a strategy to elicit a well-adapted theoretical framework (Best et al 2014). The texts were then re-read with a focus on mapping the role of and challenges facing MHSUOs informed by the perspective of the organizations' presence in invited, claimed and popular spaces for participation.…”
Section: Categorization and The Synthesizing Processmentioning
confidence: 99%
“…Smartphones can also serve to support youth empowerment by giving them a voice in their service planning in addition to facilitating emotional connections (Denby-Brinson et al, 2015). These connections could be significant sources of resilience and emotional and social development (Amichai-Hamburger, 2013;Best, Manktelow, & Taylor, 2014;Fitton, Ahmedami, Harold, & Shifflet, 2013). Providing youth with access to internet technologies can also increase their e-literacy and reduce the digital divide they may otherwise experience in their transition to young adulthood.…”
Section: Social Media In Child Welfare Practicementioning
confidence: 99%